Initial damage analysis in bone cement-stem debonding procession of cemented hip arthropsty. (January 2023) - Zhang, Lanfeng; Liu, Hongtao; Chen, Tianchi; Yuan, Feng
Graphical abstract: Highlights: It established a cement-prosthesis stem debonding experiment to analyze the initial damage process of the interfacial adhesion and explored the relationship between the inter-facial adhesion stress and slip. In terms of nondestructive testing technology detect damage of stem surface and inner bone cement, micro-morphology and micro-pores and micro-cracks and annular damage belts have been assessed and analyzed. Abstract: The initial interface debonding damage behavior of cemented hip arthroplasty was simulated and investigated through the push-in experiment. A series of nondestructive testing techniques were carried out to detect damage to the stem-cement interface and cement. Results suggested that the initial stem-cement interface debonding and cement damage were induced at femur loading early period. The cement was subjected to a combination action of shear stress and bending from a sinking stem causing a pressure-arch effect resulting in compression creep and micro-crack on the cement successively. The stem-cement interfacial friction prevent stem from sinking due to the internal shear effect caused by the cement-stem interface micro-sliding. The interface debonding procession increased at first and then became stable, which was shown in cement's creep deformation-friction-fracture model. The initial micro-cracks released damage energy which was converted into stress waves. Further, the relationship of bond stress and slippage at different locations caused different degrees of damage belt for the interface and cement. It was concluded that the combination effect of pressure arching and shear lag was the primary reason for cement's initial damage and the matrix defect affected the failure progress.